DEVELOPING ENGLISH MATERIALS WITH ISLAMIC CONTENT THROUGH TECHNOLOGICAL, PEDAGOGICAL AND CONTENT KNOWLEDGE APPROACH - Siregar, Syahreni; Yuniasih, Eka; Madkur, Ahmad (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
The integration of technology in English teaching materials is essential to meet the growing demands of modern learners including those who learn in Islamic educational contexts. This study aimed to (1) identify the English learning needs related to Technological, Pedagogical, and Content Knowledge (TPACK); (2) develop an English language textbook based on the TPACK approach; and (3) evaluate its suitability for use in Islamic higher education. Employing the Research and Development (R&D) framework by Gall et al. (2003), the study was conducted in seventh phases: research and data collection, planning, preliminary product development, preliminary field testing, product revision, main field testing, and final product revision. The participants were 77 students from three Islamic higher education institutions in Lampung, Consist of 20 students from IAI Agus Salim, 30 students from IAIN Metro, and 27 students from IAI Ma’arif Metro.The subject in this research are expert jugment and user. Data were collected through questionnaires and interviews. The data were analyzed using both qualitative and quantitative techniques.  Expert and user evaluations of the developed textbook, Basic English, demonstrated its good quality and effectiveness for use in Islamic higher education, with minor revisions recommended for optimization. The findings imply that the integration of the TPACK framework into textbook development can enhance the quality of English language learning in Islamic higher education. It is concluded that the textbook is suitable for use as an English Material in the learning process.